(untitled) (International Journal of Built Environment and Sustainability, 2025)
Haydarpasa represents a distinctive focal point within the historical urban landscape of Istanbul, shaping the city’s cultural identity and offering significant potential to balance urban conservation with sustainable development. The area’s designation as an urban conservation zone, along with zoning amendments and large-scale infrastructure projects, has raised complex challenges regarding the continuity of its transportation function, adaptive reuse of idle structures, and the long-term sustainability of heritage values amidst ongoing privatization and speculative redevelopment pressures. In this context, UNESCO’s 2011 Historic Urban Landscape (HUL) Recommendation offers a comprehensive framework for urban heritage conservation by integrating socio-cultural, environmental, and spatial dimensions. This study aims to examine the urban heritage values of Haydarpasa and evaluate sustainable conservation possibilities by proposing implementation steps and tools in line with the HUL approach. Adopting a qualitative research design, the study is supported by literature review, analysis of historical maps and documents, field observations, and institutional visits. The data were thematically analyzed according to the HUL steps, and existing problems and deficiencies in the area’s conservation were categorized and assessed. Implementation steps were prioritized based on the site’s vulnerability, planning context, and stakeholder involvement; subsequently, HUL-based tools were developed, and the strengths and limitations of the approach were discussed. The findings reveal that the conservation of Haydarpasa should not be limited to its physical structures but must also encompass its transportation function, collective memory, and urban identity. The HUL approach provides a strategic framework that enables the systematic identification of the site’s challenges and potentials, while facilitating the development of governance tools aligned with sustainable urban development.